The analysis of a battery of motor tests as a predictor of future athletic performance in children of athletic school sport classes - Prukner, V.; Sigmundova, D. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2014)
The prediction of future sport performance belongs among the most difficult tasks when choosing new talents. A great amount of attention is paid to designing a suitable battery of tests applicable to sport talent selections. Objective: The aim of this study is to analyse a battery of motor tests to assess the development of sports talents in athletic sport classes in order to suggest a battery of tests which will be able to produce an accurate assessment. Methods: The research was carried out among athletic classes in the years 2000-2007. As part of the study, 197 sixth grade students were monitored longitudinally through their ninth grade of elementary school. An entry measurement of motor skills was conducted with sixth grade students. The outgoing measurement, collected at the end of the students' ninth grade of elementary school, was in the form of four selected athletic disciplines. Results: The strongest association with overall results of athletic polyathlon was found in the standing long-jump, the 12 minute run, throwing a medicine ball and a 30 m cursory run. In boys, future performance in the athletic polyathlon can be predicted using 30 m cursory run, throwing a medicine ball, and a 12 minute run. In girls, performance in the athletic polyathlon can be predicted using 30 m cursory run and hexajump. Conclusions: An accurate prediction of future athletic performance can be made using a limited test battery which consists of, at most, three motor tests. This process efficiency can improve and economise efforts to identify talents.